A study to estimate tooth size discrepancy values specific to Saudi orthodontic patients: A systematic review and meta-analysis - Hamad Alqahtani (Elsevier, 2023)
Objective: This study aimed to establish intermaxillary tooth size ratios (overall index (OI) and anterior index (AI)) for normal occlusion and different Angle's malocclusions specific to the Saudi population and compare them to Bolton's values, which were specific to Americans. Methods: The Saudi Digital Library, PubMed, Web of Science, Cochrane Library, Scopus, and Embase were searched systematically to acquire articles which reported OI and AI for Saudi patients; inclusion and exclusion criteria were applied. Data, including author's name, publication year, city, measurement technique, number of subjects, type of occlusion, means, and standard deviations, were extracted and sorted. To assess the methodological quality of the included studies, The National Heart, Lung, and Blood Institute Quality Assessment Tool for Observational Cohort and Cross-Sectional Studies was utilized. Results: Of the 1473 articles, eight met the inclusion criteria and were included in the meta-analysis. Values for normal occlusion and Bolton's values were not significantly different. All malocclusion classes showed significant differences in the overall OI and AI values compared with Bolton's original values and values for normal occlusion, but they did not differ from each other. Gender showed an effect only on the OI ratio for Class III malocclusion. Conclusions: Bolton's original values can be used in Saudi patients only with normal occlusion. For cases with any Angle's malocclusion, we recommend using an AI value of 79.08 (±3.4) for both genders. Classes I and II, regardless of gender, have the same OI value of 92.51 (±2.82). For Class III, values of 91.97 (±2.4) for females and 93.13 (±2.6) for males can be used.